ANALYSIS OF ACCEPTANCE OF THE KREDITPLUS MOBILE USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Hilmi Luthfiansyah (Journal of Information System, Informatics and Computing, 2026)
The rapid development of financial technology in Indonesia has encouraged finance companies to adopt mobile-based services. PT. KB Finansia Multi Finance provides Kreditplus Mobile to facilitate customer financial transactions. However, the number of users remains relatively low compared to the total customer base and competitors. This study aims to analyze the effect of perceived usefulness, perceived ease of use, and attitude toward using on the acceptance of Kreditplus Mobile using the Technology Acceptance Model (TAM). This research applied a quantitative explanatory method by distributing questionnaires to 100 users selected through simple random sampling. Data were analyzed using SPSS. The results indicate that perceived usefulness, perceived ease of use, and attitude toward using have a positive and significant effect on application acceptance, both partially and simultaneously. Attitude toward using shows the strongest influence on acceptance. The findings suggest that improving service quality and enhancing application features can increase user acceptance and transaction efficiency